Audit Risk Evaluation Using Data Envelopment Analysis with Ordinal Data. (11th April 2022) - Amin, Gholam R.; El‐Temtamy, Osama; Garas, Samy
Abstract : This study examines the data envelopment analysis (DEA) model for audit risk evaluation which was initially developed by Bradbury and Rouse (2002) and reinterpreted by Davutyan and Kavut (2005). Bradbury and Rouse (2002) apply the standard DEA model for audit risk factors, including judgemental (ordinal) measures. In the presence of ordinal data, efficiency analysis in DEA requires appropriate models to be applied instead of the standard DEA model. Accordingly, audit risk evaluation based on the standard DEA model is not assessed appropriately because the risk factors are qualitative and ordinal measures. Hence, we employ an appropriate DEA model to accurately evaluate audit risk in the presence of ordinal data. In light of the prior two studies, our results demonstrate the appropriateness of the ordinal DEA model.